The Dance of Death - Strindberg, August,Mulrine, Stephen (Nick Hern Books, 2019)
Intro – Title page – Contents – Introduction – Strindberg: Key Dates – The Dance of Death Part I – Characters – ACT ONE – Scene One – Scene Two – ACT TWO – Scene One – Scene Two – The Dance of Death Part II – ACT ONE – Scene One – Scene Two – ACT TWO – Copyright and Performing Rights Information.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books